2000
DOI: 10.1109/26.843121
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Markov modeling for flat fading

Abstract: This paper investigates the properties of a method for obtaining Markov models of unspecified order to be applied to narrow-band fading channels with additive white Gaussian noise. The models are obtained by applying the context tree pruning algorithm to experimental or simulated sequences. Fading environments are identified in which the extension from first-order to higher order models is justified. The paper presents, as examples, the evaluation of the covariance function and the packet error distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…Therefore, the model designer can choose an appropriate balance between Markov model accuracy and complexity. In [17], a maximum CT depth of M = 7 was imposed when obtaining the context set and it was found that the actual context length for fading channels with f D T s ≥ 0.01 was always strictly less than seven in all constructed models.…”
Section: Ctp Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the model designer can choose an appropriate balance between Markov model accuracy and complexity. In [17], a maximum CT depth of M = 7 was imposed when obtaining the context set and it was found that the actual context length for fading channels with f D T s ≥ 0.01 was always strictly less than seven in all constructed models.…”
Section: Ctp Methodsmentioning
confidence: 99%
“…CTP is the third technique for obtaining higher-order FSMC models for fading channels, proposed in [17] and [49]. Let us first assume that a sample-by-sample quantization of the fading channel gain sequence of length N is available and the discrete-valued fading channel gain sequence is denoted by u N 1 , The CTP method is an algorithm to estimate the contexts from the training sequence u N 1 and to simplify the full tree by merging contexts.…”
Section: Ctp Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fading channel is modeled as a first order two state Markov model with certain assumptions [9], [10], [13], [14]. At any time, the channel has been in the one of the two possible states.…”
Section: The Channel Modelmentioning
confidence: 99%